DIFFUSE CORONARY ARTERY DISEASE - A CHALLENGE TO REVASCULARIZE AND THE ROLE OF CORONARY ENDARTERECTOMY - Farooq, Omer; Azam Jan; Nabila Iftikhar Awan; Usman Ghani (Journal of Ayub Medical College Abbottabad, 2022)
Coronary endarterectomy is a useful adjunct procedure in patients with diffuse coronary artery disease when isolated coronary artery bypass grafting does not permit adequate revascularization. The primary aim of this procedure is to enable ample blood flow by removing the obstructing plaque. Herein we discuss the case of a middle-aged patient who underwent coronary endarterectomy.